Pengembangan Modul Berbasis Multipel Representasi dengan Bantuan Teknologi Augmented Reality untuk Membantu Siswa Memahami Konsep Ikatan Kimia - Ririn Apriani; Andi Ifriani Harun*; Erlina Erlina; Rachmat Sahputra; Maria Ulfah (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
A good understanding of the three levels of chemical representations is required to understand the concepts of chemical bonding. However, most students are difficult to understand chemical bonding topics due to the abstract concepts and the learning resources used don’t fully integrate the three levels of chemical representations. Therefore, learning resources that cover all of the chemical representations and visualize the abstract concepts are needed. The purpose of this study is to determine the level of validity and responses of teachers and students to the developed chemical bonding module based on multiple representations assisted by AR  technology. This type of research is research and development that refers to the ADDIE instructional design model. The instrument used in this research is the sheet of validity and the response questionnaire. The collected data were analyzed using percentage analysis techniques. The product of this research is a chemical bond module based on multiple representations and an augmented reality chemistry simulator of chemical bonding application. The results of the expert's validation show that the average percentage of content, media, and language validity respectively are 99, 95, and 97% with very valid criteria, so that it can be used in the learning process. In addition, teachers and students gave a very good response to the product with a percentage of 90 and 87% consecutively. These findings indicate that the modules assisted by AR technology could support the chemistry teachers to explain the chemical bonding topic and help students visualize the abstract concepts of chemical bonds